Epidemiology of Aujeszky's Disease in Pigs in Malaysia - Gurcharan Singh, Jasbir Singh (1998)

(untitled)
Aujeszky's disease (AD) causes heavy mortalities among young pigs and great economic loss in pig farms. Despite vaccination, frequent sporadic outbreaks have been reported in different parts of Malaysia. The extent of economic loss caused by the disease is not clearly known since no detailed study has been conducted to measure the prevalence and impact of the disease in pig production. This study reports the results of a nationwide sero-epidemiological survey of the disease and attempts to determine its status among the pig population in Malaysia. It also examines some control measures that can be taken to reduce the prevalence of the disease. A commercial glycoprotein E (gE) negative enzyme-linked immunosorbent assay (ELISA) kit was used in the serological survey. The kit could detect antibodies against gE of AD virus which is present in the field strain of the virus but not in the vaccine strain. In addition, it could test large number of serum samples in a short period of time. The ELISA was evaluated with respect to the serum neutralization test (SNT) which was used as the standard reference test. The kappa value between the ELISA SIN values and SNT titres were found to be 0.95, indicating that there was a good agreement between the ELISA and SNT. It was also found that the ELISA had a high index of sensitivity (96.25%) and specificity (98.75%) comparable to SNT. The investigations therefore, confirmed the suitability of the ELISA as a practical alternative to the SNT as a mass screening test for the serodiagnosis of AD. To investigate the sero-epidemiology of AD in pigs in the country, a total of 2985 blood samples were collected from 100 pig farms in six major pig producing states of Malaysia and screened for gE antibodies against AD virus using the gE ELISA kit. Collectively, the pig population of these farms accounted for about 20.3 per cent of the pig population in West Malaysia. A widespread occurrence of the infection in the pig population in Malaysia was detected due to the high percentage (55.4%) of serological reactors in 84% of the farms surveyed. The study confirmed that AD is highly prevalent among pig herds in Malaysia and that vaccination on an individual herd basis did not minimize the spread of the virus among breeding pigs in enzuulicaHy infected, high pig density regions. To reduce the prevalence of AD, vaccination in the finishing section of farrow-to-finish herds may be warranted using more effective vaccines. In addition, an effective vaccination programme and a better biosecurity management system in the farms may be necessary to reduce the prevalence of the disease to a point where an eradication programme against AD could be initiated in Malaysia. The immune response in pigs against a disease has been known to be maximum when vaccination is given at the time of lowest maternal antibody level. To determine the optimum time of vaccination against AD in piglets in an endemic farm, blood samples were collected randomly from pigs of ages 4 to 16 weeks. The blood samples were tested for antibodies against AD by the SN test. It was found that maternal antibodies against AD persisted in pigs up to 14 weeks of age. Therefore, earlier vaccination may not be effective as the maternal antibodies may interfere with the vaccine virus. In another investigation, it was found that piglets born from parity three dams had higher levels of maternal antibodies against AD than piglets born of parity one sows. Vaccination for piglets born of dams of higher parity may therefore, be preferably at a later date than piglets born from dams of lower parity. A study using a live and an inactivated AD vaccine was conducted in fourweek-old pigs in a commercial farm to determine the effect of maternally derived antibodies on vaccination against endemic AD. It was found that maternally derived antibodies did not have a profound effect on vaccination against AD in four-week-old piglets. Furthermore, there were less economic losses in terms of mortality and body weight in vaccinated pigs as compared to non-vaccinated animals. Economic losses were lowest in pigs vaccinated with the live vaccine.